Caracterização química e comparação entre as bacias do rio Piranga e rio Santo Antônio após o rompimento da barragem de Fundão, Mariana, MG - Amanda Cristina Soares Coelho (2022)
On November 5, 2015, the Fundão dam, located in the sub-district of Bento Rodrigues, in Mariana, Minas Gerais, failed, releasing 43.7 million m³ of iron mining tailings into the Gualaxo do Norte, Carmo, and Doce rivers, all belonging to the Rio Doce Hydrographic Basin, generating concerns about the quality of the waters of these rivers. In Minas Gerais, the Doce river basin is subdivided into six Water Resources Planning and Management Units, among which are the Santo Antônio river sub-basin and the Piranga river sub-basin. These rivers affected by the tailings mud are part of the Piranga river sub-basin. Therefore, this work aims to chemically characterize, through the analysis of metals and metalloids, surface water samples from rivers in the Piranga and Santo Antônio river sub-basins, the latter being used as a reference, and to compare the data from both sub-basins to evaluate the possible impacts caused by tailings sludge. Thirteen points in the Piranga river sub-basin and 10 points in the Santo Antônio river sub-basin were selected for collection in the dry (July 2018 and July 2019) and rainy (February and March 2019) periods. The concentrations of Be, V, Cr, Mn, Co, Ni, Zn, Se, Ag, Cd, Ba, Pb and total As and dissolved Al, Fe and Cu were determined by acid digestion using the adapted SMEWW 3030E method followed by analysis by Inductively Coupled Plasma Mass Spectrometry (ICP-MS). The results were compared with the limits established by CONAMA Resolution N° 357 of 2005 for Class 2 freshwater and evaluated by means of statistical tools of multivariate analysis (PCA and HCA). A seasonal behavior was found for total Mn and dissolved Fe in the Piranga river sub-basin, which have their concentrations increased in the rainy season, exceeding the limits of legislation in some sampling stations. The dissolved Al values varied a lot during the studied periods, presenting concentrations up to 30 times higher than the maximum allowed value. In a region not affected by the mud, high levels of total As were found in all collection periods, which is justified by the presence of arsenopyrite in the region. With the results obtained, mainly for dissolved Fe and total Mn, possible impacts caused bythe rupture of the Fundão Dam in the Doce river basin were observed, even after six years of the disaster. In the dry period, Piranga river sub-basin showed behavior close to the values of the historical series of the IGAM monitoring program.